Sustainable Finance Beyond Green Bonds: Emerging Sustainable Finance Instruments for India's Green (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Traditionally, expansion in emerging economies such as India has come at the cost of environmental damage and climatic change. In recent years, concerns with sustainability and climate threats have intensified, highlighting the need for alternative development strategies. In this respect, green finance has been recognized as a pivotal mechanism for fostering sustainable economic growth by directing financial flows towards environmentally responsible and climate-friendly enterprises. This article analyses the role, difficulties and prospects of green finance in Indian economy.The secondary data utilised in this qualitative study is derived from diverse sources, including official reports, policy documents, and the latest research on sustainable and eco-friendly finance. It highlights the relevance of green finance in India for development of renewable energy, sustainable infrastructure, climate smart agriculture, rural development and expansion of environmentally sustainable financial instruments, including green bonds and investments based on Environmental, Social, and Governance (ESG) criteria.Government policies, regulatory frameworks, and institutional support have further strengthened the green finance ecosystem in the country. Besides this, the study identifies several issues like lack of awareness, low financial access, regulatory vacuum, absence of standardized credit ratings and high transaction costs that are hampering the growth of green financing in India.However, despite these limitations, green financing presents a significant opportunity to help facilitate India’s transition to a carbon-efficient and sustainable development path. to harness the promise of green finance, India must expand policy support, improve institutional coordination and enhance private sector participation.